Origin of Drosophila mushroom body neuroblasts and generation of divergent embryonic lineages. - Kunz, T.; Kraft, K.F.; Technau, G.M.; Urbach, R. (Development, 2012)
Key to understanding the mechanisms that underlie the specification of divergent cell types in the brain is knowledge about the neurectodermal origin and lineages of their stem cells. Here, we focus on the origin and embryonic development of the four neuroblasts (NBs) per hemisphere in Drosophila that give rise to the mushroom bodies (MBs), which are central brain structures essential for olfactory learning and memory. We show that these MBNBs originate from a single field of proneural gene expression within a specific mitotic domain of procephalic neuroectoderm, and that Notch signaling is not needed for their formation. Subsequently, each MBNB occupies a distinct position in the developing MB cortex and expresses a specific combination of transcription factors by which they are individually identifiable in the brain NB map. During embryonic development each MBNB generates an individual cell lineage comprising different numbers of neurons, including intrinsic ?-neurons and various types of non-intrinsic neurons that do not contribute to the MB neuropil. This contrasts with the postembryonic phase of MBNB development during which they have been shown to produce identical populations of intrinsic neurons. We show that different neuron types are produced in a lineage-specific temporal order and that neuron numbers are regulated by differential mitotic activity of the MBNBs. Finally, we demonstrate that ?-neuron axonal outgrowth and spatiotemporal innervation of the MB lobes follows a lineage-specific mode. The MBNBs are the first stem cells of the Drosophila CNS for which the origin and complete cell lineages have been determined.